High resolution electron energy loss spectroscopy of clean and hydrogen covered Si(001) surfaces: First principles calculations - PATTERSON, CHARLES (My University, 2012)
Surface phonons, conductivities, and loss functions are calculated for reconstructed (2×1), p(2×2) and c(4×2) clean Si(001) surfaces, and (2×1) H and D covered Si(001) surfaces. Surface conductivities perpendicular to the surface are significantly smaller than conductivities parallel to the surface. The surface loss function is compared to high resolution electron energy loss measurements. There is good agreement between calculated loss functions and experiment for H and D covered surfaces. However, agreement between experimental data from different groups and between theory and experiment is poor for clean Si(001) surfaces. Formalisms for calculating electron energy loss spectra are reviewed and the mechanism of electron energy losses to surface vibrations is discussed.
PUBLISHED
Keywords: Physics; Nanoscience & Materials